Modeling and Simulation of Cloud Computing with iSPD - Silva, Diogo T. da; Rodrigues, João A. M.; Manacero, Aleardo; Lobato, Renata S.; Spolon, Roberta; Cavenaghi, Marcos A. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2022: Anais do XXIII Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2022.226349, 2022)
Cloud Computing, enabled by technological enhancements and the trend for reduction of investments in IT’s physical infrastructure, is the major computing infrastructure nowadays. However, its heterogeneity makes difficult to know if the use of a given environment is efficient or not. In this context, the performance evaluation of cloud systems is useful both to clients, who need to find the best resource configuration for their applications, and to providers, who need to evaluate which scheduling and allocation policies of resources and virtual machines are most cost effective. Simulation is a good approach for this evaluation since it can be done offline. The known cloud computing simulators have issues related to their usability and modeling capability. This work extends the iconic approach for modeling and simulation offered by iSPD to cloud computing, adding icons for virtual machines and VMMs. Our results show that iSPD is faster than Cloudsim with equivalent accuracy, while providing an easier interface to model and simulate IaaS and PaaS environments.